Применение нетрадиционных регуляторов скорости для улучшения динамических характеристик стрелочного железнодорожного перевода - Акимов, Л.В.; Буряковский, С.Г.; Смирнов, В.В. (Електротехніка і електромеханіка, 2012)
The paper shows a method of designing an astatic speed control
system for a two-mass asynchronous vector-control AC railway
switch drive. A possibility of improving the drive dynamics with
a second-order speed regulator synthesized by means of a polynomial
equations method is shown.